2013
DOI: 10.1002/smll.201203164
|View full text |Cite
|
Sign up to set email alerts
|

Direct Laser‐Patterned Micro‐Supercapacitors from Paintable MoS2 Films

Abstract: Micrometer-sized electrochemical capacitors have recently attracted attention due to their possible applications in micro-electronic devices. Here, a new approach to large-scale fabrication of high-capacitance, two-dimensional MoS2 film-based micro-supercapacitors is demonstrated via simple and low-cost spray painting of MoS2 nanosheets on Si/SiO2 chip and subsequent laser patterning. The obtained micro-supercapacitors are well defined by ten interdigitated electrodes (five electrodes per polarity) with 4.5 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
395
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 481 publications
(402 citation statements)
references
References 35 publications
7
395
0
Order By: Relevance
“…Therefore, optimization of architectures would enable MoS 2 with enhanced surface area and more activated edges for ion intercalation, thereby superior performance of supercapacitors can be obtained. Another example worth noting is the work by Yang et al, 131 who reported a 2D MoS 2 -based micro-supercapacitor. This MoS 2 micro-supercapacitor was fabricated through laser patterning of a spray-coated MoS 2 film and consisted of finger-like electrodes built from curly MoS 2 nanosheets.…”
Section: Applications In Energy Storage Devicesmentioning
confidence: 99%
“…Therefore, optimization of architectures would enable MoS 2 with enhanced surface area and more activated edges for ion intercalation, thereby superior performance of supercapacitors can be obtained. Another example worth noting is the work by Yang et al, 131 who reported a 2D MoS 2 -based micro-supercapacitor. This MoS 2 micro-supercapacitor was fabricated through laser patterning of a spray-coated MoS 2 film and consisted of finger-like electrodes built from curly MoS 2 nanosheets.…”
Section: Applications In Energy Storage Devicesmentioning
confidence: 99%
“…[10,11] However, as for the emerging macro-electronics [12,13] which features cost efficiency, simple methods to fabricate solution-phase MoS2 nanosheets are favorable in a variety of applications, such as sensors, [14] photodetectors, [15,16] and supercapacitors. [17] Furthermore, patterning, [18] especially direct patterning, [17] of MoS2 at micrometer dimensions has great significance in extending their applications. As a powerful direct writing technique, [19] inkjet printing has received increasing interest in electronics.…”
Section: Introductionmentioning
confidence: 99%
“…H igh-quality and single-layered molybdenum disulfide (MoS 2 ) has been synthesized by chemical vapour deposition (CVD) over the past 2 years [1][2][3][4][5][6][7][8][9] , boosting its promise in applications involving hydrogen evolution reaction 10 , supercapacitors 11 , ultra-low power consumption field-effect transistors and phototransistor 12,13 , spintronic devices 14 , nonlinear optics 15 and biosensors 16 . CVD-grown MoS 2 atomic layers are also superior to samples prepared by mechanical exfoliation and chemical isolation methods, as continuous monolayer MoS 2 (hereafter 1H-MoS 2 ) can currently be grown at the centimetre-length scale 3,11,17,18 .…”
mentioning
confidence: 99%
“…CVD-grown MoS 2 atomic layers are also superior to samples prepared by mechanical exfoliation and chemical isolation methods, as continuous monolayer MoS 2 (hereafter 1H-MoS 2 ) can currently be grown at the centimetre-length scale 3,11,17,18 . However, concurrently with the large-scale growth of monolayer MoS 2 , variations in crystal geometries and atomic structures have been predicted and observed 19 .…”
mentioning
confidence: 99%